The influence of food composition and tag orientation on UHF RF IDentification. (April 2019) - Barge, Paolo; Biglia, Alessandro; Comba, Lorenzo; Gay, Paolo; Ricauda Aimonino, Davide; Tortia, Cristina
Abstract: Ultra-high frequency (UHF) radio frequency (RF) labelling is considered to be one of the most promising techniques for automatic identification through all food supply chain phases. However, the efficacy of RF IDentification (RFID) systems has proven critical for some food products. In this paper the role of the composition and the temperature of the food product and of the mutual label-reader orientation on identification performances is investigated. For this purpose, basic food constituents, prepared as solutions (salts, sugars, organic acids and ethanol) at different concentrations and temperatures, were considered and then the identification results were compared to those obtained from whole food products. The results show how the reading performances of UHF RFID systems are influenced by the considered parameters. The reading ranges for the identification of critical food products by UHF RFID systems can be estimated and then improved by considering the composition of the food product directly from the design phase. Highlights: The effect on tag readability of some organic and inorganic molecules was assessed. The food fat content has a positive effect on UHF tag performance. Salted and acidic foods affect the UHF tag reading area. Increasing temperature reduces UHF tag readability. The best mutual antenna-tag orientation depends on food composition.